(untitled) (Research, Society and Development, 2021)
This article is resulting from a research of the Licentiate Degree in Informatics, by the State of Santa Catarina University - UDESC, which goal was to know the methodologies and strategies used with digital technologies for the pedagogical mediation of learning and developing of Early Childhood Education children. The research started from the premise that young children already have contact with technologies in the social context, and, with just a touch on the screen, the child plays, interacts and (trans)forms their way of thinking, acting and relating with others. Based on this perspective, the following research problem was raised: How are digital technologies being used to favor the learning and development of children in Early Childhood Education? As methodological procedures, a qualitative research is presented, through a bibliographic survey and having as procedure a Systematic Literature Mapping, based on Demerval et al. (2019). The results show that there is a gap between the teacher and the digital technologies, and, consequently, their insertion in the context of Early Childhood Education is still weakened, not being understood as a potential resource for child learning and developing. The lack of continuing education for teachers is a relevant factor for resistance to the use of technological resources. On the other hand, there are studies that highlight how digital technologies can be used in pedagogical practices, allowing children to be authors, protagonists in the act of teaching and learning.